Aplicación de la entrevista cognoscitiva y de la entrevista judicial a un testigo víctima del delito de hurto (2006)
Testimony still is one of the main means to test. Traditionally it has been obtained with the standard judicial interview, taking the risk to formulate close and biased questions, interrupting and following an inappropriate sequence questions, amongst other things. This investigative work studies an alternative method to get testimony, proposed by authors like Geiselman and Fisher (1994) called cognitive interview; this method groups four general techniques of memory, plus some complementary strategies for the specific details of the recalls. Case-study was made comparing attained information with the application of the standard judicial interview and the cognitive interview to witness - victim of a fire arm robbery. A result confirms the hypothesis that guides this investigation: cognitive interview reports an increase in the information related to people, objects and events. Key words: testimony, standar judicial interview, cognitive interview, witness -victim, fire arm robbery.